2017
DOI: 10.1371/journal.pone.0174169
|View full text |Cite
|
Sign up to set email alerts
|

Reduced brain activity in female patients with non-alcoholic fatty liver disease as measured by near-infrared spectroscopy

Abstract: Patients with non-alcoholic fatty liver disease (NAFLD) have impaired health-related quality of life including physical and mental state. Near-infrared spectroscopy (NIRS) is a useful tool for evaluation of brain activity and depressive state. This study aimed to determine the brain activity of female NAFLD patients using NIRS. Cerebral oxygenated hemoglobin (oxy-Hb) concentration during a verbal fluency task (VFT) was measured using NIRS in 24 female NAFLD patients and 15 female healthy controls. The Center f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 31 publications
1
32
0
Order By: Relevance
“…cardiovascular disease, diabetes and obesity) and possibly also common pathophysiological mechanisms, including inflammation and endothelial dysfunction . Recently, NAFLD has been linked with poor cognitive function and with decreased brain activity . In addition, a study from our group has demonstrated an association between NAFLD and low total cerebral brain volume independently of multiple cardio‐metabolic factors, including diabetes, cardiovascular diseases and visceral fat .…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…cardiovascular disease, diabetes and obesity) and possibly also common pathophysiological mechanisms, including inflammation and endothelial dysfunction . Recently, NAFLD has been linked with poor cognitive function and with decreased brain activity . In addition, a study from our group has demonstrated an association between NAFLD and low total cerebral brain volume independently of multiple cardio‐metabolic factors, including diabetes, cardiovascular diseases and visceral fat .…”
Section: Introductionmentioning
confidence: 87%
“…2 Recently, NAFLD has been linked with poor cognitive function 3 and with decreased brain activity. 4 In addition, a study from our group has demonstrated an association between NAFLD and low total cerebral brain volume independently of multiple cardio-metabolic factors, including diabetes, cardiovascular diseases and visceral fat. 5 These findings are important since NAFLD prevalence is high, with estimations of around 30% in the general population and 80% among the morbidly obese.…”
Section: Introductionmentioning
confidence: 94%
“…In fact, cognitive behavioral therapy had been shown to be useful 25) , and one epidemiologic study revealed a decline in cognition in patients with NAFLD 26) . Moreover, we previously reported reduced brain activity, as measured by nearinfrared spectroscopy, in female patients with NAFLD 27) . AIH, fatty liver, and Fukushima Obstructive sleep apnea syndrome is the most famous sleep disorder in NAFLD 28) .…”
Section: -Effects Of Cognition and Sleep On Nafldmentioning
confidence: 89%
“…Using NIRS, reduced task‐induced O 2 Hb and HHb responses have been observed in several disorders, including depression and mild cognitive impairment . Of particular interest, using NIRS, one group reported decreased frontal lobe oxygenation during a verbal fluency task in patients with ulcerative colitis as well as in patients with nonalcoholic fatty liver disease but not in patients with Crohn's disease . The authors attributed these findings to altered brain activity, although it is difficult to delineate altered brain activity from altered neurovascular coupling in patients with potential cerebrovascular dysfunction …”
Section: Discussionmentioning
confidence: 99%
“…(14) Of particular interest, using NIRS, one group reported decreased frontal lobe oxygenation during a verbal fluency task in patients with ulcerative colitis as well as in patients with nonalcoholic fatty liver disease but not in patients with Crohn's disease. (31,32) The authors attributed these findings to altered brain activity, although it is difficult to delineate altered brain activity from altered neurovascular coupling in patients with potential cerebrovascular dysfunction. (8) To gain a greater understanding of how chronic immune-mediated liver inflammation impacts the brain of patients with PBC, we applied a time-frequency (coherence) analysis in conjunction with quantitative measures of hemoglobin concentration and oxygen saturation.…”
Section: Discussionmentioning
confidence: 99%